Cost efficiency analysis of logistics and warehouse business - Hasana, Rizka Amalia Nur; Purwanto, Setiyo (Universitas Ahmad Dahlan, 2024)
Cost efficiency is a key focus in various aspects of a company's operational activities, and the supply chain plays an important role in achieving this goal. To better understand how the supply chain may affect cost-effectiveness, this study examines just-in-time, total quality management, and performance measurement systems in the context of Kosambi Warehouse Area, Tangerang, which involves collecting primary and secondary data using a quantitative approach. A total of 138 respondents were selected using a simple random sampling technique. SPSS software was used to analyze the data. The findings demonstrate that just-in-time has a negative and significant effect on cost efficiency. However, total quality management has a positive and significant influence on cost efficiency. The performance measurement system has a positive and significant influence on cost efficiency.